Acetic acid‐induced colitis modulating potential of total crude alkaloidal extract of Picralima nitida seeds in rats - Sarah A. Otu‐Boakye; Kofi O. Yeboah; Eric Boakye‐Gyasi; James Oppong‐Kyekyeku; Prince D. Okyere; Newman Osafo (Immunity, Inflammation and Disease)
Abstract Purpose The total crude alkaloidal extract of Picralima nitida seeds (PNE) is known to possess anti‐inflammatory activity among other therapeutic benefits although its benefits in colitis has not been investigated. The current study therefore seeks to investigate the anti‐colitis potential of PNE using acetic acid‐induced colitis model in rats. Methods Sprague Dawley rats were treated with oral 500 mg/kg sulphasalazine or 30, 100, and 300 mg/kg of PNE daily for 8 days with induction of colitis on the fourth day with acetic acid. Rats were killed 24 h after the last treatment and whole blood was obtained from the jugular vein for hematological analysis and biochemical assays. Colons were extirpated for assessment of macroscopic and histological damage to the colon. Results Treatment with PNE protected against colonic injury induced with acetic acid by decreasing mucosal ulceration, epithelial erosion, inflammatory cell infiltration, and colonic edema. Thus, PNE preserved mucosal architecture and suppressed goblet cells depletion. Moreover, treatment with PNE was associated with improved hematological parameters and reductions in the expression of serum tumor necrosis factor‐alpha, interleukin‐1β, and p38 mitogen‐activated protein kinase. Also, PNE treatment exerted antioxidant effects by reducing nitric oxide production and increasing glutathione levels. In addition, PNE inhibited colonic lipid peroxidation by decreasing myeloperoxidase activity and malondialdehyde production. Conclusion It can be concluded that PNE attenuates intestinal oxidative and inflammatory damages following intrarectal acetic acid challenge. Thus, demonstrates potential for use in chronic intestinal inflammatory diseases such as ulcerative colitis.